The Minangkabau Exegesis Methodology Al-Da'wah Wa Al-Irsyād: Investigating The Ideas Of Abdul Lathif Syakur - Romadhona, Azizah; Marzuqi, Ammar Zain (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2024)
The Minangkabau region is known for its abundance of great scholars. One such example is Sheikh Abdul Latif Syakur, a notable figure who brought about significant changes in the Minangkabau region and bridged the gap between the young and the old. Among his many works is the commentary titled Al-Da’wah wa al-Irsyād ilā Sabīli al-Rasyād. This commentary has not been reprinted and has been studied very little. This research aims to understand the methodology used by Sheikh Abdul Latif Syakur in interpreting the Qur'an and to grasp the essence of his thoughts in this commentary. This research is a library study with a qualitative approach. Data analysis employs descriptive analytical techniques. The research finds that the commentary Al-Da’wah wa al-Irsyād ilā Sabīli al-Rasyād was written using a thematic phrase method with a socio-etiquette approach, leaning towards reasoning as a source. The commentary was written to illustrate various forms of human behavior and their consequences from Allah SWT, serving as a call to adopt good behavior and morality. Abdul Latif Syakur contextualizes this commentary in a society experiencing moral decline and devoid of any conflict between the young and the old.